The trials and joys of comparative dictionary making - Fortescue, Michael (Études/Inuit/Studies, 2007)
AbstractThe motivation behind and the methods used in putting together comparative dictionaries for language families in the Arctic and Sub-Arctic is illustrated from the author’s experience in working on the Comparative Eskimo Dictionary (Fortescue et al. 1994), the Comparative Chukotko-Kamchatkan Dictionary (Fortescue 2005) and Wakashan Comparative Dictionary (Fortescue 2007). The historical background behind these three projects is sketched and, although the focus is on them in particular, some general observations concerning the making of historical/comparative dictionaries for language families that are either endangered or possess little historical depth of attestation are presented. The broader areal framework linking the three projects is also touched upon.